Trigeminal Herpes Zoster: Case Report - Killner, Marcos André; Sum, Fernanda Noguez; Melzer, Rafaela Savio; Milani, Cintia Mussi (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Herpes Zoster is an acute, self-limiting, viral infection caused by the reactivation of the Varicella Zoster Virus (VZV) that remains latent in the dorsal root ganglion. It commonly affects the older people and immunocompromised individuals. Diabetes patients present an increased risk for Herpes Zoster due to their impaired cell-mediated immunity. Clinically it manifests with tingling, pruritus and painful vesicular eruptions along the affected nerve. The most commonly affected dermatomes are the thoracic and lumbar; trigeminal nerve can be involved and the ophtalmic nerve is the mostly affected. The diagnosis is based on clinical examination and laboratory confirmation. Treatment consists of antiviral therapy and is indicated to reduce acute pain symptoms, limit the spread and duration of the lesions, and prevent complications. The objective of the present study was to present a case report of Herpes Zoster involving the first and second division of the trigeminal nerve, in a 55 year old, male, diabetes patient.